MEASURING MALAYSIAN POLYTECHNIC PERFORMANCE USING A BOOTSTRAPPED DATA ENVELOPMENT ANALYSIS MODEL - Syed Ismail, Shariffah Nur Illiana; Salleh, Mad Ithnin; Habidin, Nurul Fadly; Mad Latip, Nor Azrin (Management Research Journal, 2015)
The purpose of this article is to investigate the effects of government regulation on higher education, particularly in the Malaysian Polytechnic scenario. The Malaysian government has put a greater attention on developing the polytechnic sector as the main provider of technical and vocational education and training (TVET) in the nation in an effort to achieve the developed nation status by the year 2020. The National Higher Education Strategic Plan (NHESP) which was implemented in 2007 has become the pivotal policy which contributes to the expansion of the polytechnic sector. This study will employ the bootstrapped Data Envelopment Analysis (DEA) model to examine the technical efficiency experiences by members of the polytechnic sector before and after the regulation.